Single-image reflection removal : from computational imaging to deep learning - Wan, Renjie (2019)
Reflection removal aims at enhancing the visibility of the background scene while removing the reflections for images taken through the transparent glass. Though it is of broad application to various computer vision tasks, it is very challenging due to its ill-posed nature and additional priors are needed to make this problem tractable. Traditional reflection removal methods solve this problem by making use of different heuristic observations or assumptions. These assumptions are seldom satisfied in practical scenarios. In this thesis, we generalize the assumptions for the reflection removal problems by using different information or imposing new constraints.